Safety and efficacy of parenteral iron in children with inflammatory bowel disease. (23rd January 2018) - Papadopoulos, Michael; Patel, Deepa; Korologou‐Linden, Roxanna; Goto, Eunice; Soondrum, Krishna; Fell, John M. E.; Epstein, Jenny
Abstract : Aims: Iron deficiency anaemia frequently complicates inflammatory bowel disease (IBD) in children and adults. Oral iron may exacerbate gastrointestinal symptoms and absorption may be insufficient in intestinal inflammation. Even where oral iron is successful, repletion of iron stores can be unacceptably slow. Intravenous iron compounds were in the past associated with serious adverse reactions and historically were considered a last resort in children. New generation preparations have a safer profile in adults, although reluctance to use them in children may persist, where safety data are lacking. We investigate the safety and efficacy of ferric carboxymaltose and iron sucrose in children. Methods: We retrospectively identified all children with IBD who received parenteral iron over a 38‐month period in a single regional referral centre. Safety, tolerability and adverse events were established by case note review. Efficacy was assessed by change in haematinic indices pre‐ and post‐treatment. Results: Forty‐one children (18 male; median age 14 years, range 3–17) received a total of 104 iron infusions. Of these, 44% (18) had Crohn's disease; 56% (23) ulcerative colitis. Thirty‐five received ferric carboxymaltose, seven iron sucrose and one both. Three children developed mild rash post infusion which resolved quickly with chlorphenamine. Mean increase in haemoglobin was 2.5 g dl –1 (0.3–5.8). Iron levels increased by a mean of 8.4 g dl –1 (1–25), transferrin saturation by 16.2% (2–47). Transferrin decreased by 0.84 g dl –1 (0.3–3.4). Conclusions: New generation parenteral iron preparations are safe, well tolerated and efficacious in children with iron deficiency anaemia and IBD.